2017
DOI: 10.3390/en10020189
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Junction Temperature Monitoring of Switching Devices with Dynamic Compact Thermal Models Extracted with Model Order Reduction

Abstract: Abstract:Residual lifetime estimation has gained a key point among the techniques that improve the reliability and the efficiency of power converters. The main cause of failures are the junction temperature cycles exhibited by switching devices during their normal operation; therefore, reliable power converter lifetime estimation requires the knowledge of the junction temperature time profile. Since on-line dynamic temperature measurements are extremely difficult, in this work an innovative real-time monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The same research gives information, according to which the maximum overloading, therefore the probable failure, occurs mostly when high current and high voltage are simultaneously applied across the device during the switch-on or switch-off periods. Additionally, the dependency of IGBTs dynamic characteristic on the temperature can be verified with modeling and simulations [12][13][14]. The proposed models have applications in converter design, mode-of-operation analysis, lifespan estimation, analysis and design of the necessary cooling system, etc.…”
Section: Introductionmentioning
confidence: 80%
“…The same research gives information, according to which the maximum overloading, therefore the probable failure, occurs mostly when high current and high voltage are simultaneously applied across the device during the switch-on or switch-off periods. Additionally, the dependency of IGBTs dynamic characteristic on the temperature can be verified with modeling and simulations [12][13][14]. The proposed models have applications in converter design, mode-of-operation analysis, lifespan estimation, analysis and design of the necessary cooling system, etc.…”
Section: Introductionmentioning
confidence: 80%
“…The first 2 data sets consist of the thermal impedance matrix derived from FEM simulations of an insulated gate bipolar transistor (IGBT) power module comprising 2 IGBTs and 2 diodes, rated at 114 A, 600 V. Parameters used for the FEM simulations are fully described in Di Napoli et al…”
Section: Algorithm Validation and Reference Case Studiesmentioning
confidence: 99%
“…The first 2 data sets consist of the thermal impedance matrix derived from FEM simulations of an insulated gate bipolar transistor (IGBT) power module comprising 2 IGBTs and 2 diodes, rated at 114 A, 600 V. Parameters used for the FEM simulations are fully described in Di Napoli et al 44 In the first case, the heatsink coefficient is set to 0.2 K/W, which can be obtained with a forced convection cooling system. This scenario has been considered to observe a wide temperature excursion.…”
Section: Algorithm Validation and Reference Case Studiesmentioning
confidence: 99%
“…Switching devices usually fail due to the junction temperature being overcome during the normal operation, as a precise estimation of the junction temperature variation is necessary. In [2], a real-time monitoring strategy to estimate the junction temperature profile considering the dissipated powers is proposed. In [3], it is shown that the Lorentz temperature distribution allows for the estimation of the temperature within a substrate using some parameters of a power electronic device and a 3D temperature distribution of the substrate.…”
Section: Introductionmentioning
confidence: 99%